SGLT2 inhibitors in patients with heart failure with reduced ejection fraction: a meta-analysis of the EMPEROR-Reduced and DAPA-HF trials - Zannad, Faiez; Ferreira, João Pedro; Pocock, Stuart J; Anker, Stefan D; Butler, Javed; Filippatos, Gerasimos; Brückmann, Martina; Ofstad, Anne Pernille; Pfarr, Egon; Jamal, Waheed; Packer, Milton (The lancet, 2020)
Background - Both DAPA-HF (assessing dapagliflozin) and EMPEROR-Reduced (assessing empagliflozin) trials showed that sodium-glucose co-transporter-2 (SGLT2) inhibition reduced the combined risk of cardiovascular death or hospitalisation for heart failure in patients with heart failure with reduced ejection fraction (HFrEF) with or without diabetes. However, neither trial was powered to assess effects on cardiovascular death or all-cause death or to characterise effects in clinically important subgroups. Using study-level published data from DAPA-HF and patient-level data from EMPEROR-Reduced, we aimed to estimate the effect of SGLT2 inhibition on fatal and non-fatal heart failure events and renal outcomes in all randomly assigned patients with HFrEF and in relevant subgroups from DAPA-HF and EMPEROR-Reduced trials. - Methods - We did a prespecified meta-analysis of the two single large-scale trials assessing the effects of SGLT2 inhibitors on cardiovascular outcomes in patients with HFrEF with or without diabetes: DAPA-HF (assessing dapagliflozin) and EMPEROR-Reduced (assessing empagliflozin). The primary endpoint was time to all-cause death. Additionally, we assessed the effects of treatment in prespecified subgroups on the combined risk of cardiovascular death or hospitalisation for heart failure. These subgroups were based on type 2 diabetes status, age, sex, angiotensin receptor neprilysin inhibitor (ARNI) treatment, New York Heart Association (NYHA) functional class, race, history of hospitalisation for heart failure, estimated glomerular filtration rate (eGFR), body-mass index, and region (post-hoc). We used hazard ratios (HRs) derived from Cox proportional hazard models for time-to-first event endpoints and Cochran's Q test for treatment interactions; the analysis of recurrent events was based on rate ratios derived from the Lin-Wei-Yang-Ying model. - Findings - Among 8474 patients combined from both trials, the estimated treatment effect was a 13% reduction in all-cause death (pooled HR 0·87, 95% CI 0·77-0·98; p=0·018) and 14% reduction in cardiovascular death (0·86, 0·76-0·98; p=0·027). SGLT2 inhibition was accompanied by a 26% relative reduction in the combined risk of cardiovascular death or first hospitalisation for heart failure (0·74, 0·68-0·82; p<0·0001), and by a 25% decrease in the composite of recurrent hospitalisations for heart failure or cardiovascular death (0·75, 0·68-0·84; p<0·0001). The risk of the composite renal endpoint was also reduced (0·62, 0·43-0·90; p=0·013). All tests for heterogeneity of effect size between trials were not significant. The pooled treatment effects showed consistent benefits for subgroups based on age, sex, diabetes, treatment with an ARNI and baseline eGFR, but suggested treatment-by-subgroup interactions for subgroups based on NYHA functional class and race. - Interpretation - The effects of empagliflozin and dapagliflozin on hospitalisations for heart failure were consistent in the two independent trials and suggest that these agents also improve renal outcomes and reduce all-cause and cardiovascular death in patients with HFrEF. - Funding - Boehringer Ingelheim.
Gesehen am 17.09.2025